Naringenin Attenuates Testicular Toxicity and Apoptosis in Rats Chronically Exposed to Mercury Chloride - Kahramanogullari, Merve; Erisir, Mine; Yaman, Mine; Kaya, Seyma Ozer; Ak, Tuba Parlak (Univ Agriculture, Fac Veterinary Science, 2025)
Mercury is an industrial toxin with detrimental effects on the reproductive system. This study explored the impact of naringenin (NAR) on testicular toxicity and apoptosis in rats chronically exposed to mercury chloride (MC). The research involved 41 adult male Wistar-Albino rats aged about 2.5 months, which were allocated into 5 groups: group 1 was a control group, group 2 received 100mg/kg of NAR, group 3 was exposed to MC, group 4 received both MC and 50mg/kg of NAR, and group 5 received both MC and 100mg/kg of NAR. For the treatments, the control group took 1mL/kg saline via intraperitoneal (ip) injection and 1mL/kg corn oil via gavage. MC was administered at 0.4mg/kg/day to the MC groups via ip, and NAR was delivered in corn oil at 50 and 100mg/kg/day to the respective NAR groups via gavage. All treatments were performed over a period of 20 days, with MC administration starting 1 hour after NAR administration. The irregularity and loss in spermatogenic cell organization, degeneration and vacuolization in tubules, edema, and congestion in interstitial areas of the testicular tissue of the MC group were alleviated by NAR administration. In addition, the increase in Caspase 3, iNOS, and eNOS immunoreactivities of the MC group were alleviated by NAR administration. In conclusion, it was found that NAR had protective and therapeutic effects against oxidative damage, histopathological changes, apoptosis, and altered spermatological parameters resulting from MC exposure in the testis, and 100mg/kg NAR provided positive effects on altered histopathological analysis, spermatological parameters, and apoptosis.
Keywords: Apoptosis; Mercury (II) Chloride; Naringenin; Oxidative Damage; Reproductive Toxicity